Multiple climate-related stressors in the tropics and beneficial changes in northern latitudes will mostly have emerged before 2050 - Audrey Brouillet; Benjamin Sultan (PLoS ONE, 2025)
Consequently to global warming, multi-sectoral impacts are observed and should intensify in the future, affecting sectors of water resources, agriculture, weather extremes and health. Related projected change signs, their possible emergences from the historical variability, and how these emergences may cumulate in time and space could thus result in severe risks or benefits for local populations. Using the world’s largest cross-sectoral climate-related impact multi-model simulations database Inter-Sectoral Impacts Model Intercomparison Project (ISIMIP), here we quantify for the first time the Time of Emergence (TOE) of historical and future simulated changes in multiple climate-related indicators at a global scale. We assess how both adverse changes (i.e. stressors) and beneficial changes (i.e. benefits) could cumulate during the century. Based on ISIMIP2b (ISIMIP phase 2b) and a low mitigation future scenario (RCP6.0), we find that many land areas are characterized by a multi-model TOE earlier than 2020 for the majority of the 10 analyzed multi-sectoral indicators. This illustrates an already reached new equilibrium-state resulting from global warming for many sectors including hydrology, agriculture and weather extremes. However, the TOE varies depending on the region and the sectoral indicator, encompassing both projected stressors and beneficial changes. The largest number of cumulated emergences of cross-sectoral stressors is projected in the tropics and include detected TOE for higher heat stress extremes, and declining crop yields. Conversely, northern mid- and high- latitudes experience the greatest number of cumulated emergences of beneficial changes, primarly associated with future crop yields increase. These cumulative emergences of stressors (in the tropics) and beneficial changes (in northern latitudes) reach their peak before 2050, indicating an early impact and related emergence on multiple sectors. Nevertheless, substantial uncertainties are exhibited in this multi-model assessment of TOE, particularly in the tropics due to a cascade of uncertainties combining climate models, impacts models, aggregated cross-sectoral impacts, and TOE detection. This study brings time constrains of multiple climate-related changes. It particularly highlights the heightened and early cumulated stressors projected in tropical regions that may further exacerbate disparities and inequalities with northern latitudes. These results also confirm the tropics paradox where fewer greenhouse gas emissions correspond to more adverse impacts from global warming. Without further mitigation and adaptation strategies, vulnerable socio-economic conditions and limited resources in these areas will amplify the negative consequences arising from early and cumulative cross-sectoral emergences, both for populations and ecosystems.